The formation of novel social category conjunctions in working memory: A possible role for the episodic buffer?. Issue 4 (20th April 2016) - Hutter, Russell R. C.; Allen, Richard J.; Wood, Chantelle
Abstract : Recent research (e.g., Hutter, Crisp, Humphreys, Waters, & Moffit; Siebler) has confirmed that combining novel social categories involves two stages (e.g., Hampton; Hastie, Schroeder, & Weber). Furthermore, it is also evident that following stage 1 (constituent additivity), the second stage in these models involves cognitively effortful complex reasoning. However, while current theory and research has addressed how category conjunctions are initially represented to some degree, it is not clear precisely where we first combine or bind existing social constituent categories. For example, how and where do we compose and temporarily store a coherent representation of an individual who shares membership of "female" and "blacksmith" categories? In this article, we consider how the revised multi-component model of working memory (Baddeley) can assist in resolving the representational limitations in the extant two-stage theoretical models. This is a new approach to understanding how novel conjunctions form new bound "composite" representations.